Clustering Of Mangrove Vegetation Based On Community Structure In Natural Mangrove Ecosystem Of Karimunjawa National Park - Eko Purnomo (SEMINAR NASIONAL PENINGKATAN MUTU PENDIDIKAN, 2020)
The importance of mangrove forest ecosystem that provide many benefits to living beings must be maintained. However, information on the distribution of vegetation and ecological functions of mangrove forest especially in Karimunjawa National Park is still very limited, thus making this research important to do. This study used "purposive sampling" method by placing the plot 10 m x 10 m to calculate the trees category, 5m x 5m for saplings and 1m x 1m for seedlings. The result of the study obtained the average density of 96.60 ind/ha tree with six number of species which is Rhizopora apiculata, Rhizopora stylosa, Sonneratia alba, Lumnitzera racemosa, Ceriops tagal, Excoecaria agallocha.